2009
DOI: 10.4048/jbc.2009.12.1.41
|View full text |Cite
|
Sign up to set email alerts
|

The Changes of the Histologic and Biologic Markers Induced by Neoadjuvant Chemotherapy in Locally Advanced Breast Cancer

Abstract: Purpose: Neoadjuvant chemotherapy (NAC) has become the standard treatment for locally advanced breast cancer. The postoperatively adjuvant systemic treatment is based on the status of the histological and biological markers of either the pre-NAC or the post-NAC. There have been several reports that have demonstrated the changes of the histological and biological markers after NAC. The aim of this study is to investigate the effects of NAC on the expression of the histological and biological markers of breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Interestingly, we found that the serum HER2 level was elevated in 15.8% of recurrent cases with an HER2-negative primary tumor, which had been considered false-positive cases in other studies. This conversion rate of serum HER2 in our study is very similar with the rate of tissue HER2 change after disease recurrence in other studies; HER2 status was found to change after disease recurrence in 7% to 32% of cases [2][3][4][5][6]23]. Taken together, these results suggest that elevated serum HER2 levels could reflect the conversion of tissue HER2 expression, and HER2 targeted therapy could be helpful in relapsed patients with HER2-negative primary tumors and elevated serum HER2 levels during the follow-up period.…”
Section: Journal Of Surgical Oncologysupporting
confidence: 91%
“…Interestingly, we found that the serum HER2 level was elevated in 15.8% of recurrent cases with an HER2-negative primary tumor, which had been considered false-positive cases in other studies. This conversion rate of serum HER2 in our study is very similar with the rate of tissue HER2 change after disease recurrence in other studies; HER2 status was found to change after disease recurrence in 7% to 32% of cases [2][3][4][5][6]23]. Taken together, these results suggest that elevated serum HER2 levels could reflect the conversion of tissue HER2 expression, and HER2 targeted therapy could be helpful in relapsed patients with HER2-negative primary tumors and elevated serum HER2 levels during the follow-up period.…”
Section: Journal Of Surgical Oncologysupporting
confidence: 91%